(untitled) (Journal of the College of Education for Women, 2025)
In literature, places frequently serve as more than just physical settings. They actively participate in the plot of the literary text and represent the historical, social, and cultural aspects of the inhabitants who live in them. In August Wilson’s Radio Golf, Ester’s house and Pittsburgh’s Hill District are important locations that capture the struggles and lived experiences of African Americans. Instead of being blank backgrounds, these places are storied settings that are filled with cultural heritage and memory. This paper explores the conflict between erasure and remembrance in Hill District and Aunt Ester’s house. As a neighborhood on the edge of change, Hill District is portrayed in the play as being in danger of being cut off from its historical roots by gentrification and economic development plans. On the other hand, Ester’s house acts as a sacred, nearly mythical place that keeps spiritual continuity and decades of African American memory. It turns into a moral compass that forces characters to face their heritage before pursuing a future aim. This paper embraces the theory of the human geographer, Yi-Fu Tuan, showing how Wilson transforms places into archives of historical value by blending resistance into physical structures. This study highlights the value of cultural preservation in the face of displacement and contributes to current academic discussions in African American geographies, memory studies, and literary urbanism. Ultimately, by focusing on the Hill District and Ester’s house, Radio Golf offers a deep reflection on how a place shapes its people’s identity and collective memory.